A contractor's guide to the FIDIC conditions of contract - Robinson, Michael D. (Consulting engineer) (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell, 2011)
This guide will help the contractor & rsquo;s staff overcome some of the difficulties encountered on a typical international contract using FIDIC forms. The majority of FIDIC-based contracts use the Red Book (Conditions of Contract for Construction), so this book concentrates on the use of those particular forms. Supplementary comments are included in Appendix C for the Yellow Book (Plant & Design-Build) recommended for use where the contractor has a design responsibility. The Contractor is represented on site by the Contractor & rsquo;s Representative who carries the overall responsibility for all.
Review of the FIDIC conditions for construction (CONS) (the 'Red Book') -- Activities and duties of the FIDIC contractor's representative discussed in the same order as they appear in the FIDIC conditions of contract -- Activities and duties of the FIDIC contractor's representative summarised and arranged in time sequence.
Includes bibliographical references and index.
Print version record.
Keywords: Construction contracts; Engineering contracts; Architectural contracts; Standardized terms of contract; Architectural contracts; Construction contracts; Engineering contracts; Standardized terms of contract; Electronic books